Medical Negligence Concept in Malaysia: A Legal Study - Hidayani, Poppy Putri; Muhammad Hatta; Sumiadi; Zulfan (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2023)
Doctors could not guarantee regarding recovery of their patient. Doctors can only work according to the knowledge they have. However, the failure of doctors to cure patients often accused of doing medical negligence. The issue of medical negligence is not a new phenomenon in the doctoral profession, and even medical negligence has become a global issue. Although Malaysia is one of the few countries where medical emergencies occur, but each year the number of medical negligence increases. The Bolam v Friern Hospital Management Committee 1957 case has long been a measure of cases in medical negligence in Malaysia. However, after the Federal Court's decision in the case of Foo Fio Na v Dr Foo Sook Mun & Anor 2007, there was a change in the approach taken by a Malaysian court, which showed that the courts in Malaysia now no longer prioritize the Bolam test in medical negligence cases. In Civil Act 1956 and the Medical Act 1971, medical negligence is only regulated in a civil aspect only so that the guilty physician will be punished to pay compensation to the patient. Generally, medical negligence cases are resolved through court. However, it is difficult to prove the negligence done by the doctor and the length of time needed to tackle the case of medical negligence through the court has prompted physicians and patients to bring their case through the mediation forum